Application of nanofluids for enhanced waste heat recovery: A review. (June 2021) - Olabi, A.G.; Elsaid, Khaled; Sayed, Enas Taha; Mahmoud, Mohamed S.; Wilberforce, Tabbi; Hassiba, Raid J.; Abdelkareem, Mohammad Ali
Abstract: Heat is the most common form of energy either in final or intermediate forms, with the latter enabling energy conversion to other useful forms. Heat is primarily sourced from fossil fuels representing about 80% of the global primary energy supply. However, heat is usually associated with high energy losses as waste heat (WH). Energy conversion losses amount to about 88% of the global energy supply, with about 50% of such losses as WH. Waste heat recovery (WHR) is aiming at recovering such energy losses either as heat, work, or power. Nanofluids (NFs) have been evolved recently as high-performance heat transfer fluids. The use of NFs to improve WHR is very promising in terms of recovery efficiency, potential, and feasibility. For instance, the use of graphene/water NF for WHR from combustion stack gas has resulted in about 25% increase in energy recovery efficiency. Similarly, the use of nanoparticles enhanced phase change material for WHR from steelworks has successfully been used to drive the distillation process increasing the energy capacity of the system by about 2.76 times. The simulations of using Ag/Pentane NF for organic Rankine cycle has increased the overall system efficiency from 11% to 14% at 30% lower exergy destruction and 14% less carbon footprint. This review aims at discussing the application of NFs for improved WHR in different applications. The review discusses first the different WH sources and recovery approaches. Then, the properties and performance of NFs for WHR are thoroughly discussed. The review discusses as well the different thermo-economic and environmental aspects of WHR using NFs. The potential challenges and future aspects associated with the application of NFs for WHR are additionally discussed. Finally, the review provides constructive recommendations and conclusions, shading light on research needs and future perspectives to optimize the performance of such systems. Graphical Abstract: ga1 Highlights: Different WH sources and recovery approaches are summarized. The application of NFs for improving WHR is discussed. Thermo-economic and environmental aspects of WHR using NFs are elaborated. Future perspectives to optimize the performance NFs in WHR are highlighted.